Coevolutionary Dynamics of Organic-Inorganic Interactions, Hydrocarbon Generation, and Shale Gas Reservoir Preservation: A Case Study from the Upper Ordovician Wufeng and Lower Silurian Longmaxi Formations, Fuling Shale Gas Field, Eastern Sichuan Basin. (22nd December 2020) - Jin, Zhijun; Nie, Haikuan; Liu, Quanyou; Zhao, Jianhua; Wang, Ruyue; Sun, Chuanxiang; Wang, Guanping
Abstract : Shale gas deposits are self-sourced, self-accumulating, and self-preserving in the Upper Ordovician Wufeng Formation and Lower Silurian Longmaxi Formation of the Fuling Shale Gas Field in the eastern Sichuan Basin. They were both seemingly mixed by secondary oil cracking and kerogen cracking gases during the high maturation window. The reservoir space primarily consists of mineral pores and organic matter (OM) pores, and the shale gas was mainly trapped by a high-pressure system. In this study, the Fuling O3 w -S1 l Shale Gas Field in the eastern Sichuan Basin was used as a case study to discuss the coevolutionary process and organic-inorganic interactions of hydrocarbon generation, accumulation, and preservation. The results indicate that the processes and mechanisms of organic-inorganic interactions and coevolution of hydrocarbon generation and reservoir preservation are quite different among the shale graptolite zones (GZ) with respect to hydrocarbon generation, types and characteristics of shale gas reservoirs, seal characteristics, and their spatiotemporal relations. In the WF2-LM4 GZ, the favorable OM, biogenic authigenic quartz and organic-inorganic interactions are highly coupled, leading to the high level of coevolution demonstrated within the field, as well as to the favorable conditions for shale gas accumulation. Conversely, the overlying LM5-LM8 GZ seemingly exhibits early densification and late charge and has a reverse mode of reservoir development (i.e., low degree of coevolution). These two coevolutionary processes were conducive to the development of a high degree of spatiotemporal matching between the reservoir (i.e., WF2-LM4 GZ) and the seal (i.e., LM5-LM8 GZ). This is due to underlying differences in their coevolutionary histories. The synthetic work presented here on the coevolutionary processes and mechanisms of formation for organic-inorganic interactions and hydrocarbon generation and reservoir preservation reveals insights into the driving mechanisms of shale gas enrichment, providing a basis for effectively predicting favorable enrichment intervals for shale gas worldwide.